Implementing long-term care systems in the Americas: a regional strategy - Pablo Villalobos Dintrans; Mallika Mathur; Emmanuel González-Bautista; Jorge Browne; Carolina Hommes; Enrique Vega (Pan American Health Organization, 2021)
The Region of the Americas is facing accelerated demographic and epidemiological changes. As these trends will continue in future years, long-term care needs are expected to rise. How can countries respond to these challenges? We propose that countries in the Region should invest in the implementation of long-term care systems. Considering the heterogeneity in the Region, we propose a strategy based on three components: (i) understanding the problem; (ii) thinking about solutions; and (iii) building support and consensus. Depending on each country's needs and capacities, these three elements suggest short-term and long-term actions and goals, from generating better information on long-term care needs to the implementation of long-term care systems. Longterm care is a relevant issue for the Region today. The task is challenging, but countries need to embrace it and move forward before it is too late.